Between Community and State:: Practicing Public Health in Cape Breton, 1938-1948 - Mullally, Sasha (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2009)
Abstract Using the experiences of a Nova Scotia Public health nurse, Phyllis Lyttle, this article shows how practical considerations and local needs largely defined rural public health work in the early years of the provincial system (1938-1948). Examining public health reports and community narratives reveals how Lyttle expanded her role to include primary care and midwifery services – a role similar to that of a late-20th-century nurse practitioner – in response to the needs and expectations of the local population and the local general practitioner, C. Lamont MacMillan.